المسائل التي خالف فيها قانون الأسرة القطري مذهب الإمام أحمد بن حنبل ـ في المواد القانونية المتعلقة بالطلاق البدعي أنموذجا - Zakariyah, Habeebullah; Almarri, Ali Mubarak Safran (UNISSA Digital Journal - Sultan Sharif Ali Islamic University, 2018)
تهدف هذه الورقة إلى بلورة المسائل التي خالف فيها قانون الأسرة القطري مذهب الإمام أحمد بن حنبل ـ رحمه الله تعالى ـ، وخاصة في المواد القانونية المتعلقة بالطلاق البدعي، وتناول الباحث هذه المسائل مبينا أسباب عدم أخذ القانون بالمذهب، وتم استخدام المنهج التحليلي المقارن في بيان أوجه الاختلاف بين المذهب والقانون القطري، وخلص الباحثان إلى نتائج أهمها:عدم خروج قانون الأسرة عن مذهب الإمام أحمد أو مذهب الجمهور، وأقوال أهل العلم الراسخين فيه، مثل ابن حزم، وابن تيمية، وابن القيم، وغيرهم من الأعلام في الغالب اللهم إلا في مسألة عدم إيقاع طلاق الثلاث ثلاثًا كما في المذهب، ومسألة عدم وقوع الطلاق في العدة بخلاف المذهب، ومسألة عدم وقوع الطلاق في الحيض أو طهر مسها فيه كما في المذهب. على أن القانون القطري اعتمد في مخالفته على الأقوال التي تحقق مصلحة الأسرة، وعدم تشتتها وضياعها. ****************************************************** The idea of this research is summed up in the discussion of the issues in which Qatari family law violated the doctrine of Imam Ahmad ibn Hambal, may Allah almighty have mercy on him, and the legal articles relating to an innovative divorce in particular, whether being it innovative of time, such as divorce during the menstrual period or puerperal period or during the waiting period, or innovative of number, such as three divorces consecutively or inconsecutively. All which will be presented by the researcher along with the reasons for not taking the doctrine of Ahmad in the law, and that will be in the sections relating to the comparison between the doctrine and law. The researcher concluded at the end of the research to several results, among which most important are as follows: The family law does not depart from the doctrine of Imam Ahmad or the doctrine of majority of scholars (al-Jumhῡr) and also from the opinions of erudite scholars, such as Ibn Hazm, Ibn Taymiyyah, Ibn al-Qayyim and other renowned scholars. Disagreement of the family law with the doctrine of Imam Ahmad in several matters, i.e. non-consideration of three divorces as three as it is stipulated in the doctrine, non-occurrence of divorce during waiting period in contrary to the doctrine, non-occurrence of divorce during the menstrual period or period of purity in which sexual intercourse occurs as it is stated in the doctrine. In all articles studied in this research, the family law subscribed to the opinions that are in the interest of the family, and not to be dispersed or lost.